Crystallisation behaviour of palm oil: application of fractal analysis on crystal network of palm oil products / Zaliha Omar - Omar, Zaliha (2006)
Refined bleached deodorised palm oil (RBDPO) was blended with 4 to 25% (w/w) fully hydrogenated palm oil (HPO). The effect of blending, crystallisation kinetics and storage temperatures on the physical, chemical, morphological and macroscopic rheological properties of these samples were studied. The microstructural level of crystal networks of the samples were also quantified via fractal geometrical methods by rheological measurement (Df) and image analysis (Db). The results showed a significant (p<0.05) increase in the slip melting point (SMP) from 37 to 53°C and maximum solid fat content (SFC) of 69% at 5°C and completely melted within 45 to 55°C with HPO added. However, X-ray diffraction result showed that, the pure RBDPO and HPO blends at all ratios were stabilised in the β′ polymorphic form. Crystallisation kinetics studied using the Avrami model indicated that, pure RBDPO and the blends crystallised in a rod-like growth mechanism from instantaneous nucleation (Avrami exponent n=2) at 10°C and by a disc-like growth mechanism with n = 3 from sporadic nucleation at 15 and 20°C. Blends with 4% of HPO at 15°C crystallised with a smaller crystallisation rate constant (k= 0.00432 k-1min), lower nucleation activation free energy (∆Gc,= 1.02 kJ/mol) and a shorter induction time (ι) using the Fisher-Turnbull model. During storage at 15, 20 and 25°C, there was an increase in storage modulus (G′) and hardness index (HI). At 15°C, fractal dimensions (Df and Db) of pure RBDPO by both methods respectively decreased from Df=2.50 to 2.41 and Db=1.38 to 1.22 . The same trend was observed for fractal dimension of the crystal network at 20 and 25°C. However, there was no significant (p>0.5) increase in the SFC of the microstructures of pure RBDPO and HPO blends. The β′ crystal of the microstructures of the blends showed better dispersion and smaller clusters than pure RBDPO. An increase in storage modulus (G′), hardness index (HI) and compression force (g) indicated that the crystal network of the blends are becoming more highly structured with increasing storage time. This implies that posthardening had occurred without transformation of polymorphic form and is due to crystal networking after the crystallisation process